Polypharmacy, medication adherence and medication management at home in elderly patients with multiple non-communicable diseases in Thai primary care - Vatcharavongvan, Pasitpon; Puttawanchai, Viwat (Family Medicine & Primary Care Review, 2017)
Background . Polypharmacy among elderly patients in primary care settings is a global phenomenon that has not been well examined in Thailand. Objectives . To determine (i) the prevalence rate of polypharmacy (using ≥ 5 medications) among elderly Thai patients ≥ 60 years of age who were diagnosed with multiple non-communicable diseases (NCDs) in primary care, (ii) medication adherence and (iii) quality of home medication management. Material and methods . The electronic medical records of eligible patients were reviewed to obtain demographic data, current medications, medical diagnoses and medical outcomes such as blood pressure. Those with polypharmacy were interviewed at their homes using structured questionnaires to examine medication adherence and medication management at home. Data was collected between September 2014 and April 2015. Results . Of the 397 participants, 146 (36.8%) had polypharmacy. Those with polypharmacy were more likely to have type 2 diabetes mellitus, poor disease control and more NCDs. High rates of poor medication adherence (61%) and poor medication management (60.2%) at home were found in the polypharmacy group, but these factors were not associated with poor disease control (p = 0.169 and p = 0.683, respectively). Conclusions . More than one-third of the sample of Thai elderly with multiple NCDs in primary care were recipients of polypharmacy. Of those with polypharmacy, almost two-thirds reported poor medication adherence and poor medication management at home. Strategies to decrease unnecessary polypharmacy and improve both medication adherence and home management are essential in this patient group.